Collins primary literacy: pupil book 1b - Hiatt, Kay; Stones, Brenda (Collins Educational London, 2008)
Collins Primary Literacy Pupil Book 1B features fiction from Georgie Adams, poetry from Pamela Mordecai, and exciting non-fiction on the Eden Project and the farm. Pupil Book 1B covers a wide variety of text types and topics, and provides engaging activities to help you deliver the objectives of the renewed Framework.